Connection of BANK1, Tolerance, Regulatory B cells, and Apoptosis: Perspectives of a Reductionist Investigation - Le Berre, Ludmilla; Chesneau, Mélanie; Danger, Richard; Dubois, Florian; Chaussabel, Damien; Garand, Mathieu; Brouard, Sophie (Frontiers in Immunology, 2021)
BANK1 transcript is upregulated in whole blood after kidney transplantation in tolerant patients. In comparison to patients with rejection, tolerant patients display higher level of regulatory B cells (Bregs) expressing granzyme B (GZMB+) that have the capability to prevent effector T cells proliferation. However, BANK1 was found to be decreased in these GZMB+ Bregs. In this article, we investigated 7 different transcriptomic studies and mined the literature in order to make link between BANK1, tolerance and Bregs. As for GZMB+ Bregs, we found that BANK1 was decreased in other subtypes of Bregs, including IL10+ and CD24hiCD38hi transitional regulatory B cells, along with BANK1 was down-regulated in activated /differentiated B cells, as in CD40-activated B cells, in leukemia and plasma cells. Following a reductionist approach (1), biological concepts were extracted from BANK1 literature and allowed us to infer association between BANK1 and immune signaling pathways, as STAT1, FcγRIIB, TNFAIP3, TRAF6, and TLR7. Based on B cell signaling literature and expression data, we proposed a role of BANK1 in B cells of tolerant patients that involved BCR, IP3R and PLCG2, and a link with the apoptosis pathways. We confronted these data with our experiments on apoptosis in total B cells and Bregs, and this suggests different involvement for BANK1 in these two cells. Finally, we put in perspective our own data with other published data to hypothesize two different roles for BANK1 in B cells and in Bregs.